PENGARUH KINERJA KARYAWAN UNTUK KEPUASAN PELANGGAN J&T - Aditya Risky Sahari; Menur Kusumaningtyas (PUTRA JAWA PUBLISHER, 2024)
The success of a business today can be supported by a strategy of offering quality services with good service quality and high performance. It is not a difficult or complicated matter for the service that the company can provide, but if it is not optimal it can affect the quality of the company because of its sensitive nature. Employee performance is measured based on several main indicators, namely competence, communication, work ethic and quality of services provided. Data was collected through a survey involving approximately 100 customer respondents. Quantitative methods were used as an analytical method for this research, by collecting data results from surveys via customer respondents. The research results must show that employee performance has a significant and positive influence on customer satisfaction. Competence indicators and service quality were found to be the most influential factors for customer satisfaction. This research suggests that service companies focus on employee training and development to improve their performance, which in turn will increase customer satisfaction. These findings provide practical implications for managers in designing employee performance improvement strategies in an effort to achieve higher customer satisfaction.